Error Analysis of Mudzakkar and Muannats Usage among Indonesian University Students Learning Arabic - Ahmad Fikri; Harisah Harisah (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2026)
Grammatical gender is one of the most challenging morphosyntactic features of Arabic, requiring agreement between masculine (mudzakkar) and feminim (muannats) nouns and other sentence elements, including verbs, adjectives, demonstratives, and pronouns. This study aims to analyze students` error patterns in the use of mudzakkar and muannats and identify the factors contributing to these errors. A descriptive qualitative approach employing error analysis was used. Data were collected through a  written tests administered to 28 students enrolled in an Arabic Language Education program at an Indonesian university. The data were analyzed through error identification, classification, and interpretation. The findings indicate that the most frequent errors involved nouns adjective gender agreement, followed by subjects verbs agreement and the use of demonstratives and pronouns. These errors were mainly attributed to first language interference, limited vocabulary, and insufficient contextual practice. The findings highlights the importance of contextualized, usage based Arabic grammar instruction to improve learners` mastery of gender agreement.